A Marine-Biology-Centric Definition of Ocean Connectivity and the Law of the Sea - Elise Johansen (Cappelen Damm Akademisk NOASP, 2021)
The inter-connectedness of marine ecosystems has been repeatedly acknowledged in the relevant literature as well as in policy briefs. Against this backdrop, this article aims at further reflecting on the question of to what extent the law of the sea takes account of or disregards ocean connectivity. In order to address this question, this article starts by providing a brief overview of the notion of ocean connectivity from a marine science perspective, before taking a closer look at the extent to which the law of the sea incorporates the scientific imperative of ocean connectivity in the context of four examples: (i) straits, (ii) climate change and ocean acidification, (iii) salmon and (iv) the ecosystem approach to fisheries. Tying the findings of the different examples together, this study concludes by stressing the need of accommodating ocean connectivity not only in the interpretation and implementation of the existing law (of the sea) but also in its further development.